The incidence of tuberculosis and its relation to social inequalities: Integrative Review Study on PubMed Base - Maria Rita Bertolozzi; Renata Ferreira Takahashi; Francisco Oscar de Siqueira França; Paula Hino
Abstract Objective: to identify how the literature presents the relation between tuberculosis and social inequalities. Method: integrative review in which the combination of the descriptors "tuberculosis" and "social iniquity" guided the search for articles available in PubMed. A total of 274 articles were identified, and after reading the title and abstract, 13 studies were selected. The empirical material was analyzed according to the hermeneutics, highlighting the variables related to social inequalities, seeking to understand the main themes that embody the association between tuberculosis and social inequalities. Results: In general, the literature presents the social inequalities as factors that can interfere in the cure and/or control of the disease, such as age, income, unemployment, unskilled labor, access to health services, among others. Therefore, it does not include a deeper relationship between the organization of society and the production of the disease. Conclusion and implications for practice: A comprehensive understanding of tuberculosis disease is required, in order to expand interventions to support the control and elimination of the disease and, above all, the reduction of social inequalities. The understanding of tuberculosis as a disease enables expanding strategies to face it.